Integrative study of chicken lung transcriptome to understand the host immune response during Newcastle disease virus challenge - Vanamamalai, Venkata Krishna; Priyanka, E.; Kannaki, T. R.; Sharma, Shailesh (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionNewcastle disease is one of the significant issues in the poultry industry, having catastrophic effects worldwide. The lung is one of the essential organs which harbours Bronchus-associated lymphoid tissue and plays a vital role in the immune response. Leghorn and Fayoumi breeds are known to have differences in resistance to Newcastle disease. Along with genes and long non-coding RNAs (lncRNAs) are also known to regulate various biological pathways through gene regulation.MethodsThis study analysed the lung transcriptome data and identified the role of genes and long non-coding RNAs in differential immune resistance. The computational pipeline, FHSpipe, as used in our previous studies on analysis of harderian gland and trachea transcriptome was used to identify genes and lncRNAs. This was followed by differential expression analysis, functional annotation of genes and lncRNAs, identification of transcription factors, microRNAs and finally validation using qRT-PCR.Results and discussionA total of 8219 novel lncRNAs were identified. Of them, 1263 lncRNAs and 281 genes were differentially expressed. About 66 genes were annotated with either an immune-related GO term or pathway, and 12 were annotated with both. In challenge and breed-based analysis, most of these genes were upregulated in Fayoumi compared to Leghorn, and in timepoint-based analysis, Leghorn challenge chicken showed downregulation between time points. A similar trend was observed in the expression of lncRNAs. Co-expression analysis has revealed several lncRNAs co-expressing with immune genes with a positive correlation. Several genes annotated with non-immune pathways, including metabolism, signal transduction, transport of small molecules, extracellular matrix organization, developmental biology and cellular processes, were also impacted. With this, we can understand that Fayoumi chicken showed upregulated immune genes and positive cis-lncRNAs during both the non-challenged and NDV-challenge conditions, even without viral transcripts in the tissue. This finding shows that these immune-annotated genes and coexpressing cis-lncRNAs play a significant role in Fayoumi being comparatively resistant to NDV compared to Leghorn. Our study affirms and expands upon the outcomes of previous studies and highlights the crucial role of lncRNAs during the immune response to NDV.ConclusionThis analysis clearly shows the differences in the gene expression patterns and lncRNA co-expression with the genes between Leghorn and Fayoumi, indicating that the lncRNAs and co-expressing genes might potentially have a role in differentiating these breeds. We hypothesise that these genes and lncRNAs play a vital role in the higher resistance of Fayoumi to NDV than Leghorn. This study can pave the way for future studies to unravel the biological mechanism behind the regulation of immune-related genes.